STRATEGI KOMUNIKASI PEMBERDAYAAN MASYARAKAT DESA (Implementasi Program PKKP Dinas Pemuda, Olahraga dan Pariwisata Jawa Tengah Tahun 2018 di Desa Tambakselo, Grobogan) - Ali Damsuki (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2019)
This study discusses the communication strategies of PKKP 2018 participants (Youth Care and Leadership Program) of the Department of Youth and Sports of Central Java Province in empowering rural communities, especially for youth who are included in the youth group and PKK in Tambakselo village, Grobogan, Central Java. village. Interest in what communication strategies are made by 2018 PKKP participants so that the community empowerment program in the Tambakselo village in Central Java Grobogan district can be established, realized and even transforms the community towards a brighter future. The purpose of this study was to obtain an overview of the communication strategies carried out by PKKP 2018 participants. The empowerment of village communities was decided on for Youth Organizations and PKK, which mostly consisted of young people and girls who had the enthusiasm to develop the village. Starting from the field of small and medium enterprises to the field of education that will be promoted in the village. The research approach used in this study is to use the case study method as one of the qualitative traditions. From the research it is known that community empowerment activities in Tambakselo, Grobogan district, Central Java have been carried out and have succeeded in changing the level of community awareness in developing their own regions through the PKKP program and other village programs.